In situ Listeria monocytogenes biocontrol and sensory attributes enhancement in raw beef meat by Enterococcus lactis. Issue 9 (9th June 2020) - Ben Braïek, Olfa; Smaoui, Slim; Ennouri, Karim; Ben Ayed, Rayda; Hani, Khaled; Mastouri, Maha; Ghrairi, Taoufik
Abstract: The enterocin P‐producing Enterococcus lactis strain Q1 was directly added at 10 7 CFU/g in refrigerated raw beef to evaluate its effectiveness in the control of Listeria monocytogenes EGDe 107776 proliferation. Furthermore, sensorial evaluation of the quality of treated beef meat samples with the enterococcal protective culture was performed basing on color, odor, and appearance parameters for 14 days. As a result, it was demonstrated that the enterocin P‐producing E. lactis Q1 strain led to a remarkable reduction ( p < .05) of L. monocytogenes in beef meat by 6.47 ± 0.30 log units after 7 days and 7.25 ± 0.35 log units below the control after 14 days, then remained stable up to 28 days of cold storage. Also, E. lactis Q1 strain improved significantly ( p < .05) the organoleptic quality of treated beef sample. Hence, E. lactis Q1 clearly indicates its efficiency to be used as protective agent in a wide range of meat products. Practical applications: Preserving meat using new bacteriocinogenic lactic acid bacteria is an important agenda to ensure consumer safety. The present study showed the ability of an enterocin P‐producing strain named E. lactis Q1, added in raw beef meat during cold storage, to inhibit L. monocytogenes and improve meat sensory properties. Hence, E. lactis Q1 can be used in the future to develop healthy meat products with better shelf life and quality.